Back pain and radiological changes in the thoraco-lumbar spine of athletes. A long-term follow-up - Lundin, O.; Hellstrom, M.; Nilsson, I.; Sward, L. (Scandinavian Journal of Medicine & Science in Sports, 2001)
From 1996 to 1999, back pain and radiological changes in the thoraco-lumbar spine were investigated in 134 former top athletes, representing wrestling, gymnastics, soccer and tennis (age 27-39 years) and a group of 28 non-athletes of comparable age. This is a long-term follow-up investigation of a previous radiological study of the spine with clinical correlation. Despite significantly more radiological abnormalities among the athletes, they did not report higher frequency of back pain than the non-athletes. A decrease in disc height or new disc height reduction in one or more of the intervertebral discs between the two examinations correlated significantly with back pain at follow-up.